SOME RESULTS ON LAGUERRE TRANSFORM IN TWO VARIABLES - Salehbhai, I.A.; Shukla, A.K. (Italian Journal of Pure and Applied Mathematics, 2015)
An attempt is made to investigate some results on Laguerre transform in two variables [8]. In this paper, Laguerre transform of some particular functions and integral formulas have been obtained.